Una historia del mundo - Marr, Andrew, 1959- (Pretérita, 2018)
This book takes readers from the Mayans to Mongolia, from the kingdom of Benin to the court of the Jagiellonian kings of Poland. Traditional histories of this kind have tended to be Euro-centric, telling mankind's story through tales of Greece and Rome and the crowned heads of Europe's oldest monarchies.